ANALYZING OF STUDENT’S INTEREST IN SPEAKING ENGLISH SKILL IN PESANGGAR, PEGANTENAN, PAMEKASAN - Riski Arisandi (Universitas Madura, 2023)
This study aims to determine the level of students' interest in English, especially speaking skills and to find out the reasons why students are not interested in rural areas. The benefit of this research is that students in rural areas can be more aware of how important English is, and keep the spirit of learning even though the school condition is still not sufficient in terms of facilities and infrastructure. The method in this study uses a qualitative method which in this study uses a questionnaire and interviews to obtain data which in this study involves several tenth grade (X) and eleventh grade (XI) students who have been recommended by the teacher as samples. The results of this study are students in rural areas tend not to be interested in English because there are several factors and weaknesses that exist in schools and in individual students themselves.